2016
DOI: 10.3389/fpls.2016.00300
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Silencing of Two Arginine Decarboxylase Genes Alters Development in Arabidopsis

Abstract: Polyamines (PAs) are small aliphatic polycations that are found ubiquitously in all organisms. In plants, PAs are involved in diverse biological processes such as growth, development, and stress responses. In Arabidopsis thaliana, the arginine decarboxylase enzymes (ADC1 and 2) catalyze the first step of PA biosynthesis. For a better understanding of PA biological functions, mutants in PA biosynthesis have been generated; however, the double adc1/adc2 mutant is not viable in A. thaliana. In this study, we gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Plant polyamines are also an important class of plant growth regulators. Arginine decarboxylase (ADC) 29 , S-adenosylmethionine synthetase (SAMS), S-adenosylmethionine decarboxylase (SAMDC) 30 , Spermidine synthase (SPDS) 31 , polyamine oxidase (PAOs) are key enzymes in polyamine metabolism. ADC , SAMDC and SPDS expression are up-regulated in early flowering sample.…”
Section: Discussionmentioning
confidence: 99%
“…Plant polyamines are also an important class of plant growth regulators. Arginine decarboxylase (ADC) 29 , S-adenosylmethionine synthetase (SAMS), S-adenosylmethionine decarboxylase (SAMDC) 30 , Spermidine synthase (SPDS) 31 , polyamine oxidase (PAOs) are key enzymes in polyamine metabolism. ADC , SAMDC and SPDS expression are up-regulated in early flowering sample.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we observed a significant increase of PA content in OsHSFA3-overexpressing plants than in WT under both control as well as drought stress conditions ( Figure 6). This increased PA level was correlated with increased expression of AtADC1, AtADC2, SPDS1 and SPMS genes, which are the key genes regulating the PA level [19][20][21]. In addition, we showed that OsHSFA3 can bind to AtADC1 and OsADC via a yeast one-hybrid assay ( Figure 6).…”
Section: Discussionmentioning
confidence: 78%
“…The enzyme arginine decarboxylase (ADC) catalyzes arginine to agmatine, which is the precursor of putrescine and higher polyamines (PAs), such as spermidine and spermine. Several genes have been reported to control the production of polyamines in plants [18,19]. In Arabidopsis thaliana, ADC only has two paralogues, AtADC1 and AtADC2 [20].…”
mentioning
confidence: 99%
“…ADC1 and ADC2 expression is increased in adc2 and adc1 mutant plants, respectively, after P. viridiflava infection (Rossi et al 2015). However, no similar reciprocal increase was observed for basal ADC1 and ADC2 expression under non‐stressed conditions (Rossi et al 2015; Sánchez‐Rangel et al 2016). The most unequivocal evidence of functional redundancy is the observation that Arabidopsis adc1 adc2 double mutants are embryo lethal, indicating that having at least one functional ADC gene is essential for normal seed development (Urano et al 2005).…”
Section: Introductionmentioning
confidence: 83%